2019
DOI: 10.1002/jcp.28523
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of microRNA‐22‐3p against retinal pigment epithelial inflammatory damage by targeting NLRP3 inflammasome

Abstract: NLRP3, as a crucial inflammasome component, plays important roles in age‐related macular degeneration. Though some activators of NLRP3 have been studied, microRNAs (miRNAs) which potentially regulate NLRP3 messenger RNA (mRNA) have not been fully explored in retinal pigment epithelial (RPE) cells and retinopathy. In this study, by miRNA microarray profiling and bioinformatic analysis, we identified that four miRNAs, miR‐4286, miR‐223‐3p, miR‐365a, miR‐22‐3p, may target NLRP3 mRNA in RPE inflammatory damage in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The expression of miR‐22‐3p is closely correlated to the NLRP3 inflammasome. Some studies reported that miR‐22‐3p plays an essential protective role in the inflammatory injury and cell apoptosis by inhibiting the mRNA and protein expression of NLRP3, Caspase‐1, and IL‐1β through targeting NLRP3 22‐24 . However, one study revealed that miR‐22‐3p could inhibit Sirtuin 1 protein expression and promote the high expression of inflammatory cytokines tumor necrosis factor‐α, IL‐1β, and IL‐8, which are vital for the development of inflammation 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR‐22‐3p is closely correlated to the NLRP3 inflammasome. Some studies reported that miR‐22‐3p plays an essential protective role in the inflammatory injury and cell apoptosis by inhibiting the mRNA and protein expression of NLRP3, Caspase‐1, and IL‐1β through targeting NLRP3 22‐24 . However, one study revealed that miR‐22‐3p could inhibit Sirtuin 1 protein expression and promote the high expression of inflammatory cytokines tumor necrosis factor‐α, IL‐1β, and IL‐8, which are vital for the development of inflammation 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between miR-22-3p and MMP-3, MMP-7 was observed, suggesting that miR-22-3p can regulate metastasis, and its regulation of MMPs is one of the mechanisms. MMP-3 and MMP-7 are the most associated factors with miR-22-3p and the most important downstream genes of miR-22-3p (Hu et al, 2019;Lv et al, 2018). MMP-7 has the strongest effect on the degradation of extracellular matrix, and when MMP-7 is activated, which can regulate interstitial angiogenesis, epithelial-mesenchymal transformation and cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA (miRNA), a sort of single-stranded noncoding small RNA, is known to negatively regulate gene expression posttranscriptionally, either by inhibiting translation or destabilizing its target transcripts. [14][15][16] Recent studies have identified that NLRP3 can be regulated by several miRNAs in various diseases, including miR-22-3p, 17 miR-21, 18 miR-132, 19 miR-181a, 20 and so on. However, few studies have investigated which miRNAs might target and regulate NLRP3 in macrophages during liver injury.…”
Section: Introductionmentioning
confidence: 99%